PENGEMBANGAN HANDOUT BERGAMBAR DISERTAI NETWORK TREE PADA MATERI STRUKTUR DAN FUNGSI JARINGAN HEWAN SEMESTER I KELAS XI UNTUK SMA - Yulriska, Sefreni; Sudirman, Sudirman; Megahati, RRP. (Pendidikan Biologi, 2014)
ABSTRACT Handout picture of a network tree with one of the teaching materials that help students in understanding the subject matter . This study aims to determine the validity and practicalities handout picture with network tree. This research is the development of the use of 4 - D Models consisting of 4 stages namely, define, design, develop, and disseminate. However , in this disseminate stage was not involved. This handout is validated by 3 lecturer and high school teachers PGRI 1 Padang. Test practicalities by 2 teachers and 20 students of class XI science. Data were analyzed with the technique and the percentage of processed descriptively. Handouts produced has a valid criterion is 81.57 %. Handouts are also said to be practically used by teachers and students with an average of 77.44 % and 81.25 %. Therefore, it can be concluded that the network tree with pictorial handouts on material structure and function of animal tissues generated are valid and practical.